2020
DOI: 10.1186/s40100-020-00161-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of US sugar prices on the financial performance of US sugar-using firms

Abstract: The effect of the United States (US) sugar program on sugar-using firm profitability from 2000 to 2017 is examined using firm financial data and the relative US-to-world sugar price ratio. Return on assets and market-to-book ratio proxy for firm financial performance. The regression results provide statistical evidence that as the US sugar price increases relative to the world sugar price, sugar-using firm financial performance improves. This is likely a result of sugar-using firms passing higher sugar costs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The goal of this paper is to determine factors influencing SCP prices with a particular interest on understanding the role of input sugar prices. Trejo-Pech et al (2020) was the first known research to examine the relationship between US sugar prices and sugar-using firm performance as measured by firms' ROAs and MTB ratios. It was found that as the ratio of US wholesale refined beet sugar price to the world refined sugar (US-to-world) price increased, firms' ROAs increased.…”
Section: Conceptual Framework and Hypothesized Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The goal of this paper is to determine factors influencing SCP prices with a particular interest on understanding the role of input sugar prices. Trejo-Pech et al (2020) was the first known research to examine the relationship between US sugar prices and sugar-using firm performance as measured by firms' ROAs and MTB ratios. It was found that as the ratio of US wholesale refined beet sugar price to the world refined sugar (US-to-world) price increased, firms' ROAs increased.…”
Section: Conceptual Framework and Hypothesized Resultsmentioning
confidence: 99%
“…Trejo-Pech et al (2020, page 14) concluded their research with a possible explanation of, "US sugar-using firms must pass on higher costs to consumers when relative prices increase or do not pass on discounts to consumers when relative sugar prices decrease." We examine this outstanding question using a unique data set of SCP prices as a dependent variable, rather than using firm profits (ROA and MTB ratios) as a dependent variable like Trejo-Pech et al (2020), and by including sugar prices as an independent variable. Thus, this research will directly estimate whether higher US sugar prices are passed on to consumers while controlling for other relevant possible determinants of food prices.…”
Section: Conceptual Framework and Hypothesized Resultsmentioning
confidence: 99%
See 3 more Smart Citations